Sovereignty in International Law - Czubik, Paweł (International Law From A Central European Perspective, 2022)
Sovereignty is a concept enshrined in the theory of international law. As an attribute of independent states, it constitutes the basis for their autonomous activities in the international legal space. Virtually the entire contemporary primary conceptual apparatus of jus gentium has been developed around this notion. The principle of the sovereignty of all states results in their mutual sovereign equality. Sovereignty of states is protected by the prohibition against intervening in their internal affairs and the prohibition on the use of force in international law. The state exercises its sovereign rights over the population in a given territory. Sovereignty is associated with the right to freely shape relations within the state, and it means legal independence from external factors. Freedom of action by sovereign states means, first of all, the freedom to conclude international agreements between states and to assume obligations. Such actions do not infringe on states’ sovereignty; rather, they are an expression of it whereby the state exercises its legal capacity. This is because only coerced actions undertaken against the will of a given entity could be perceived as an attack on a state’s sovereignty. Of course, the sovereignty of a state can be eliminated by its own free will—this entity may join (unite with) another state entity, thus losing its sovereignty. However, it is not possible to confer sovereignty on another entity as a result of activities consisting in the transfer of only a limited scope of state powers. Even the transfer of a part of territory under the administration of another state does not deprive the transferor of sovereignty over the territory, to which it is entitled under international law. States may also delegate their competences to other subjects of international law—other states (most often this is the case of microstates, which are unable to perform all standard functions of the state, especially in the field of external relations, economic management, or the administration of justice) or international organizations. Such a delegation of competences does not imply a revocation of sovereignty. It occurs by way of an international agreement between entities transferring competences, or an agreement between the founding states of an international organization. At any time, the member states can withdraw the delegated competences or dissolve the organization. Even if the scope of the delegated competences is considerable and the organization begins to play an important role by assuming a supranational position in the area of the adopted internal law, it does not become a sovereign entity. Theories that suggest otherwise are essentially based on confusing the concept of sovereignty with the concept of competence. KEYWORDS: state in international law, sovereign equality, territory, competences, transfer of state powers, international organization